Implementation of Housing Provision Policy for Low-Income Communities in Bandung City West Java Province - Arief, Indra Maulana Syamsul; Ilham, H.Muh; Tjenreng, M.B Zubakhrum; Ruhana, Faria (Yayasan Riset dan Pengembangan Intelektual, 2024)
The high backlog gap between the number of houses built and the housing needs of low-income communities (MBR), limited land, and lack of budget, are problems faced by the local government in providing housing for MBR in Bandung City. Therefore, this study aims to analyze the implementation of the policy of providing housing for MBR in Bandung City along with supporting and inhibiting factors, and to formulate a model for implementing housing policies for MBR. The study used a qualitative research design with a descriptive method. Primary data were collected through interviews with key informants at the Bandung City Housing and Settlement Service, non-participant observation, and secondary data were collected through documentation studies. The analysis technique used descriptive analysis techniques including data condensation, data presentation and drawing conclusions. The results of the study are as follows: 1) The policy of providing housing for MBR is not yet optimal which is not supported by the availability of budget resources, limited human resources and inadequate equipment facilities; 2) Policy implementation is supported by regional regulations, support from the central government and the private sector, and cooperation between the government and public agencies (KPBU), while the inhibiting factors are limited budget, limited land, high land prices, community rejection, and urbanization; 3) The implementation model of the housing provision policy for MBR in Bandung City (“Masagi Policy Implementation Model”) was formulated by researchers, with the novelty of adjustments to the normative basis of the policy, funding scheme, development implementers, supervision, and recommendations for the use of state land with the HGB scheme. In addition, the novelty of the model is the need for leadership and sustainability in the dimensions of the policy implementation model that will increase the effectiveness of housing provision for MBR.